Fashion Marketing on Instagram Platform - Aina, Salma Qurrotu (International Journal of Research Innovation and Entrepreneurship, 2021)
Fashion photography that was previously distributed through printed media such as magazines, is now also distributed online through social media such as Instagram. Seeing this change in trends, this study aims to examine the form, visual appeal, and messages conveyed by fashion photography in Instagram’s content. This study used a descriptive qualitative research approach with a visual analysis methods. Observations and interviews were used for the data collection, sourced from fashion marketing accounts on Instagram, and from other Instagram users with photography and fashion education backgrounds. The results showed that the form of fashion marketing photography varied depending on the concepts and products being sold. Photos that were unique, different, and use good compositions were favored by the followers. Each photo had its own theme and message concept. In addition, each photo showed that anyone can look cool and attractive if they use the fashion products shown in the photos. So, the fashion photography used in Instagram content should look unique and different, with good photographic composition, as well as easy-to-understand messages.